Progress in diagnosis and treatment of autoimmune pancreatitis - YIN Tao (Linchuang Gandanbing Zazhi, 2015)
Autoimmune pancreatitis (AIP) is a special type of chronic pancreatitis that originates from an autoimmune-mediated mechanism. AIP has unique radiological, serological, and histopathological features, often accompanied by peripancreatic lesions. AIP may be easily confused with pancreatic cancer and cholangiocarcinoma. It is necessary to diagnose AIP while integrating a variety of clinical indicators. Steroid therapy should be performed for patients diagnosed with AIP, and surgical treatment can be selected if necessary.